Agile Software Development - Manjunath, R; Nagashree, RA (International Journal of Computer Sciences and Engineering, 2025)
Successful software is one which provides quality product in given cost and time. Delivering quality software in definite time is a difficult task. Traditional software processes are heavy weight, giving importance to documentation and are rigid making them difficult to apply to different software projects. Agile has become one of the big buzzwords in the software development industry. To put it simply, Agile development or lightweight methods are less documentation oriented and more code oriented stating that source code is the most important document. Agile is a different way of executing software development teams and projects. Agile approaches help the teams respond to unpredictability through incremental, iterative work cadences or otherwise known as “sprints”. Agile methodologies are an alternative to waterfall, or traditional sequential development. This software can be used in development stage, open collaboration and process adaptability in the process of project development. With a minimal work in different stages can improve planning of the project. . This paper discusses a few agile processes, the philosophy driving them and challenges faced while implementing them and mainly focuses on seeking alternative approach to traditional project management.